(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
This article examines the state of hydrobiocenosis communities and the chemical composition of the water of the Muynak Bay of the Southern Aral Sea. Assessment of changes in the composition of phytoplankton, zooplankton, zoobenthos and ichthyofauna